2016
DOI: 10.1016/j.ejor.2015.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic forecasting with discrete choice models: Evaluating predictions with pseudo-coefficients of determination

Abstract: Probabilistic forecasts from discrete choice models, which are widely used in marketing science and competitive event forecasting, are often best evaluated out-of-sample using pseudo-coefficients of determination, or pseudo-R 2 s. However, there is a danger of misjudging the accuracy of forecast probabilities of event outcomes, based on observed frequencies, because of issues related to pseudo-R 2 s. First, we show that McFadden's pseudo-R 2 varies predictably with the number of alternatives in the choice set.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Literature on sports betting has shown that odds can be used to predict the outcome of horse races (Ma et al, ; Sung, McDonald, and Johnson, ), hockey (Cantinotti, Ladouceur, and Jacques, ), tennis (McHale and Morton, ; Lisi and Zanella, ), the Ryder Cup (Maher, ), the Olympics (Chen, Li, and Zeng, ), and, of course, football (Andersson, Memmert, and Popowicz, ; Boulier and Stekler, ; Forrest, Goddard, and Simmons, ; Hvattum and Arntzen, ; Khazaal et al., ; Leitner, Zeileis, and Hornik, ; Štrumbelj and Šikonja, ). Constantly changing odds in all these sports are provided by bookmakers based on a combination of their expert knowledge and the wagers of fans, who place bets in the hope of beating the odds.…”
mentioning
confidence: 99%
“…Literature on sports betting has shown that odds can be used to predict the outcome of horse races (Ma et al, ; Sung, McDonald, and Johnson, ), hockey (Cantinotti, Ladouceur, and Jacques, ), tennis (McHale and Morton, ; Lisi and Zanella, ), the Ryder Cup (Maher, ), the Olympics (Chen, Li, and Zeng, ), and, of course, football (Andersson, Memmert, and Popowicz, ; Boulier and Stekler, ; Forrest, Goddard, and Simmons, ; Hvattum and Arntzen, ; Khazaal et al., ; Leitner, Zeileis, and Hornik, ; Štrumbelj and Šikonja, ). Constantly changing odds in all these sports are provided by bookmakers based on a combination of their expert knowledge and the wagers of fans, who place bets in the hope of beating the odds.…”
mentioning
confidence: 99%